PENGARUH KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN - RUMAWAS, WEHELMINA (Sam Ratulangi University, 2015)
AbstractLeadership is regarded as one of the important assets in the company, because thecompany's leadership can be used to determine how the company's current environmentalconditions, and also to estimate how the environment will change and how to anticipate andtake advantage of these changes. However, many companies do not know, how to acquire,manage, and utilize the knowledge leads to achieve job satisfaction of employees in thecompany.The objective of this study is to analyze and explain the effect of Leadership towardJob Satisfaction. Research location is conducted in Bitung in the cooking oil companies. PTMulti Nabati Sulawesi.The research belongs to explanatory research. The samples are taken by usingproportionate random sampling technique and the size of the samples to be determined 100respondents. The data collecting technique is questionnaire. The data is analyzed by usinglinear regression.Key words: Leadership, Job Satisfaction